Avaliação do vigor de sementes de beterraba (Beta vulgaris L.) - Silva, Josué Bispo da [UNESP] (2003)
The use of seeds with high physiological potential is fundamental for the establishment of the crop, because it represents one of the major factors that will provide to the crop the possibility of expressing your maximum productive potential. The use of appropriate vigor tests becomes indispensable to evaluate the physiological potential of the produced and marketed seed lots. Therefore, this work was carried out in order to study the accelerated aging and deterioration controlled tests as methods to evaluate the vigor of beet seeds (Beta vulgaris L.), correlating their results with seedlings field emergency. The vigor of beet seeds can, therefore, be evaluated efficiently using accelerated aging, both traditional and in saturated salt solution and controlled deterioration tests.